Elimination of Unwanted Electro-magnetic Noise in a GTEM Cell for IC Emission Measurements - Chua, K.L.; Jenu, M.Z.M.; Wong, M.O.; Ying, S.H. (Journal of Engineering and Technology (JET), 2013)
The IEC 61967 standards suggest an integrated circuits (ICs electromagnetic emission measurement technique by mounting IC test board on TEM/GTEM cell wall. It appears that the method has limited device under test (DUT) rotation in horizontal position and neglected vertical polarization while rotating in horizontal position. In general, the electromagnetic emission of a device at an observation point is contributed by both the horizontal and vertical polarizations. The limitation can be overcome by conducting the emission test in Gigahertz Transverse Electromagnetic Mode (GTEM). However, supporting components on the board and interface cable are the major concerns which may contribute unwanted noise to interfere with the measurement. In this paper, we present an effort to tackle these crucial matters in the setup in order to quantify IC electromagnetic emission in GTEM cell with application of basic electromagnetic compatibility (EMC) measurement approaches such as shielding, grounding and suppression using ferromagnetic material. The results show strong evidence on the effectiveness of the technique proposed to ensure reliable IC emission measurement in GTEM cell.